PERSEPSI ORANG TUA SISWA DAN GURU TENTANG PENDIDIKAN DASAR GRATIS - Syamsu Alam Hamid (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2012)
This study aimed to determine 1 ) whether they ( parents and teachers ) have a clear understanding of the free education policy 2 ). How their perceptions about the meaning of